Modeling the Impact of Advertisement-Image Congruity on Applicant Attraction. - Baum, M; Schäfer, M; Kabst, Rüdiger (Human Resource Management.)

The effectiveness of recruitment advertisement and recruitment websites: Indirect and interactive effects on applicant attraction. - Baum, M; Kabst, Rüdiger (Human Resource Management (HRM).)

Recruitment Process Outsourcing and Applicant Reactions: When Does Image Make a Difference? - Wehner, M C; Giardini, A; Kabst, Rüdiger (Human Resource Management.)

The effect of culture on the responsiveness of firms to mimetic forces: Imitative foreign joint venture entries into China, 1985–2003. - Li, C; Parboteeah, P (Journal of World Business)

The influence of cultural context on the relationship between gender diversity and team performance: A meta-analysis. - Schneid, M; Isidor, R; Li, C; Kabst, Rüdiger (International Journal of Human Resource Management.)

Participatory Budgeting: Findings from Germany. - Weber, H I; Vogt, S; Eberz-Weber, L M; Steinmetz, Holger; Wagner, S A; Walther, F; Weber, P; Kabst, Rüdiger (International Journal of Public Administration in the Digital Age.)

Requirements for IT Security Metrics - An Argumentation Theory Based Approach - Yasasin, Emrah; Schryen, Guido (23rd European Conference on Information Systems (ECIS 2015))

A Multi-Theoretical Literature Review on Information Security Investments using the Resource-Based View and the Organizational Learning Theory - Weishäupl, Eva; Yasasin, Emrah; Schryen, Guido (International Conference on Information Systems)
The protection of information technology (IT) has become and is predicted to remain a key economic challenge for organizations. While research on IT security investment is fast growing, it lacks a theoretical basis for structuring research, explaining economic-technological phenomena and guide future research. We address this shortcoming by suggesting a new theoretical model emerging from a multi-theoretical perspective adopt-ing the Resource-Based View and the Organizational Learning Theory. The joint appli-cation of these theories allows to conceptualize in one theoretical model the organiza-tional learning effects that occur when the protection of organizational resources through IT security countermeasures develops over time. We use this model of IT security invest-ments to synthesize findings of a large body of literature and to derive research gaps. We also discuss managerial implications of (closing) these gaps by providing practical ex-amples.
Keywords: Information Security; Investment; Literature review; Resource-based View; Organi-zational Learning Theory; Multi-theoretical Perspective

IT Security Investments Through the Lens of the Resource-Based View: A new Theoretical Model and Literature Review - Weishäupl, Eva; Yasasin, Emrah; Schryen, Guido (23rd European Conference on Information Systems (ECIS 2015))

Towards an Economic Approach to Identity and Access Management Systems Using Decision Theory - Weishäupl, Eva; Kunz, Michael; Yasasin, Emrah; Wagner, Gerit; Prester, Julian; Schryen, Guido; Pernul, Günther (2nd International Workshop on Security in highly connected IT Systems (SHCIS?15))
Nowadays, providing employees with failure-free access to various systems, applications and services is a crucial factor for organizations? success as disturbances potentially inhibit smooth workflows and thereby harm productivity. However, it is a challenging task to assign access rights to employees? accounts within a satisfying time frame. In addition, the management of multiple accounts and identities can be very onerous and time consuming for the responsible administrator and therefore expensive for the organization. In order to meet these challenges, firms decide to invest in introducing an Identity and Access Management System (IAMS) that supports the organization by using policies to assign permissions to accounts, groups, and roles. In practice, since various versions of IAMSs exist, it is a challenging task to decide upon introduction of an IAMS. The following study proposes a first attempt of a decision support model for practitioners which considers four alternatives: Introduction of an IAMS with Role-based Access Control RBAC) or without and no introduction of IAMS again with or without RBAC. To underpin the practical applicability of the proposed model, we parametrize and operationalize it based on a real world use case using input from an expert interview.
Keywords: Identity and Access Management; Economic Decision Making; Information Systems; Information Security Investment; Decision Theory

IT-Sicherheit: Ökonomisch Planen und Bewerten - Schryen, Guido; Weishäupl, Eva (Managementkompass)

Theory of Knowledge for Literature Reviews: An Epistemological Model, Taxonomy and Empirical Analysis of IS Literature - Schryen, Guido; Wagner, Gerit; Benlian, Alexander (International Conference on Information Systems (ICIS))
Literature reviews play an important role in the development of knowledge. Yet, we observe a lack of theoretical underpinning of and epistemological insights into how literature reviews can contribute to knowledge creation and have actually contributed in the IS discipline. To address these theoretical and empirical research gaps, we suggest a novel epistemological model of literature reviews. This model allows us to align different contributions of literature reviews with their underlying knowledge conversions - thereby building a bridge between the previously largely unconnected fields of literature reviews and epistemology. We evaluate the appropriateness of the model by conducting an empirical analysis of 173 IS literature reviews which were published in 39 pertinent IS journals between 2000 and 2014. Based on this analysis, we derive an epistemological taxonomy of IS literature reviews, which complements previously suggested typologies.
Keywords: Literature review; Research methods/methodology; Theory of knowledge

Resource Planning in Disaster Response - Decision Support Models and Methodologies - Schryen, Guido; Rauchecker, Gerhard; Comes, Martina (Business & Information Systems Engineering (BISE))

Writing qualitative IS literature reviews ? Guidelines for synthesis, interpretation and guidance of research - Schryen, Guido (Communications of the AIS)

Discovering (Hidden) Pathways within the Framework of Design Based Research (DBR) - Developing and "Arena of Innovation" in VET Contexts - Frehe, Petra; Kremer, H.-Hugo (Crossing Boundaries in Vocational Education and Training: Innovative Concepts for the 21st Century. Conference Proceedings.)

Stochastic pumping of a polariton fluid - Assmann, Marc; Bayer, Manfred (PHYSICAL REVIEW A)
We investigate the response of a polariton laser driven slightly off-resonantly using light fields differing from the routinely studied coherent pump sources. The response to driving light fields with thermal and displaced thermal statistics with varying correlation times shows significant differences in the transmitted intensity, its noise, and the position of the nonlinear threshold. We predict that adding more photons on average may actually reduce the transmission through the polariton system.

Electric field effect on optical harmonic generation at the exciton resonances in GaAs - Brunne, D.; Lafrentz, M.; Pavlov, V. V.; Pisarev, R. V.; Rodina, A. V.; Yakovlev, D. R.; Bayer, M. (Physical Review B)
An electric field applied to a semiconductor reduces its crystal symmetry and modifies its electronic structure which is expected to result in changes of the linear and nonlinear response to optical excitation. In GaAs, we observe experimentally strong electric field effects on the optical second (SHG) and third (THG) harmonic generation. The SHG signal for the laser-light k vector parallel to the [001] crystal axis is symmetry forbidden in the electric-dipole approximation, but can be induced by an applied electric field in the vicinity of the 1s exciton energy. Surprisingly, the THG signal, which is allowed in this geometry, is considerably reduced by the electric field. We develop a theory which provides good agreement with the experimental data. In particular, it shows that the optical nonlinearities for the 1s exciton resonance are modified in an electric field by the Stark effect, which mixes the 1s and 2p exciton states of opposite parity. This mixing acts in opposite way on the SHG and THG processes, as it leads to the appearance of forbidden SHG in (001)-oriented GaAs and decreases the crystallographic THG.

Impact of nanomechanical resonances on lasing from electrically pumped quantum dot micropillars - Czerniuk, T.; Tepper, J.; Akimov, A. V.; Unsleber, S.; Schneider, C.; Kamp, M.; Höfling, S.; Yakovlev, D. R.; Bayer, M. (Applied Physics Letters)
We use a picosecond acoustics technique to modulate the laser output of electrically pumped GaAs/AlAs micropillar lasers with InGaAs quantum dots. The modulation of the emission wavelength takes place on the frequencies of the nanomechanical extensional and breathing (radial) modes of the micropillars. The amplitude of the modulation for various nanomechanical modes is different for every micropillar which is explained by a various elastic contact between the micropillar walls and polymer environment.

Photon-Statistics Excitation Spectroscopy of a Quantum-Dot Micropillar Laser - Kazimierczuk, T.; Schmutzler, J.; Aßmann, M.; Schneider, C.; Kamp, M.; Höfling, S.; Bayer, M. (Physical Review Letters)
We introduce photon-statistics excitation spectroscopy and exemplarily apply it to a quantum-dot micropillar laser. Both the intensity and the photon number statistics of the emission from the micropillar show a strong dependence on the photon statistics of the light used for excitation of the sample. The results under coherent and pseudothermal excitation reveal that a description of the laser properties in terms of mean input photon numbers is not sufficient. It is demonstrated that the micropillar acts as a superthermal light source when operated close to its threshold. Possible applications for important spectroscopic techniques are discussed.

Novel mechanisms of optical harmonic generation on excitons in semiconductors - Yakovlev, D. R.; Warkentin, W.; Brunne, D.; Mund, J.; Pavlov, V. V.; Rodina, A. V.; Pisarev, R. V.; Bayer, M. (Nonlinear Optics and Applications IX)